Effect of veneering technique on shear strength of porcelain veneered zirconia (PVZ): finite element analysis - Nurul Hannani Abdul Hadi,; Nashrah Hani Jamadon,; Meor Iqram Meor Ahmad,; Muhammad Sufiyan Amril,; Nurul Shayhiera Aminuddin,; Yew, Hsu Zenn (Penerbit Universiti Kebangsaan Malaysia, 2024)
Veneering technique is discussed as one of the reasons for chipping of porcelain veneered zirconia (PVZ) restorations, which impacts their longevity and success. This study aims to evaluate the effect of veneering technique; heat-pressed, and hand-layered, on the shear bond strength of PVZ ceramics through finite element analysis. Six cylindrical bilayer material model configurations were analysed; two types of zirconia, IPS e.max® ZirCad (Z) and Luxen Zr (L) and each veneered with three porcelain types, Shofu Vintage ZR (V), IPS e.max® Ceram (C), IPS e.max® Zirpress (P), with dimensions of (10 mm x 1.2 mm) and (5 mm x 3 mm), respectively. The force for three-dimensional model configurations were fixed at 5 kN. The results show that heat-pressed groups (ZP and LP) haveslightly higher bond strength value 49.12 MPa and 49.03 MPa, compared to hand-layered groups (ZC, LC, ZV,and LV), measuring 48.87 MPa with 0.5% difference at maximum. Bond strength in MPa underwent varianceanalysis, revealing a significant influence of ceramic material on mean values (p = 0.0017). Thus, the highest stressconcentrations occur at the edges of the load application points, gradually decreasing as the distance from the pointof load application increases. Results indicate that heat-pressed technique is better than hand-layered veneeringtechnique due to its effectiveness in strong adhering veneer to the zirconia core.